Energy and touch-information for body-worn ubiquitous computing. (21st July 2009) - Cheok, Adrian David; Peiris, Roshan Lalintha; Fernando, Charith Lasantha; Fernando, Owen Noel Newton; , Khoo Eng Tat
Addressing a key issue in ubiquitous computing and power generation, this paper presents several novel techniques that use the human body itself as an energy resource for power generation and as a biological data network. Particularly focusing on power from human walking, we conducted comprehensive studies determining and comparing critical factors such as efficiencies and power generation levels generated for real generation techniques. Additionally, we present a breakthrough development of low-cost miniature circuits with significantly improved efficiencies ideal for such generation application. This paper also describes novel systems of ubiquitous personal area networks that exchange digital information by physical touch.